2008
DOI: 10.1111/j.1467-9450.2008.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Swedish norms for word fluency tests: FAS, animals and verbs

Abstract: Verbal fluency tests are useful measures of acquired language impairment and cognitive decline of various etiologies. The aim of this study was to provide normative data for the Swedish population on the three verbal fluency tests, FAS, Animals and Verbs. A group of 165 healthy participants ranging from 16 to 89 years of age were assessed with the verbal fluency tests and tests of level of intellectual functioning. The sample was stratified by education, age and gender. Level of education had a substantial inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
113
1
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(141 citation statements)
references
References 31 publications
13
113
1
10
Order By: Relevance
“…The subject was cued with a letter (F, A, S) and had to generate as many words as possible within a minute (FAS-test, Friedman et al, 1998;Loonstra et al, 2001). The Swedish norm, depending on age and gender, is predictive of intellectual level (Tallberg et al, 2008). Lastly, a Reading task selected from the Swedish exam for university students was used.…”
Section: Disorders (Bedömning Av Subtila Språkstörningar [Assessment mentioning
confidence: 99%
“…The subject was cued with a letter (F, A, S) and had to generate as many words as possible within a minute (FAS-test, Friedman et al, 1998;Loonstra et al, 2001). The Swedish norm, depending on age and gender, is predictive of intellectual level (Tallberg et al, 2008). Lastly, a Reading task selected from the Swedish exam for university students was used.…”
Section: Disorders (Bedömning Av Subtila Språkstörningar [Assessment mentioning
confidence: 99%
“…This might have occurred because their samples only included elderly (Machado et al, 2009) or young and middle-aged adults (Buriel et al, 2004;Villodre et al, 2006). Nevertheless, other studies have investigated different age groups and have not found the age effect either (Hughes & Bryan, 2002;Steiner et al, 2008;Tallberg et al, 2008). Such discordant fi ndings may be explained by differences in the sample sizes, inclusion criteria, and statistical analyses used in each study.…”
Section: Age Effects In Verbal Fluency Task Performancementioning
confidence: 55%
“…Conversely, there is evidence of an education effect, showing that highly educated outperform low education individuals (Buriel, Gramunt Fombuena, Böhm, Rodés, & Peña-Casanova, 2004;Butman et al, 2000;Kosmidis, Vlahou, Panagiotaki, & Kiosseoglou, 2004;Peña-Casanova et al, 2009;Rami, Serradell, Bosch, Villar, & Molinuevo, 2007;Van Der Elst, Van Boxtel, Van Breukelen, & Jolles, 2006;Villodre et al, 2006). However, some investigations present different fi ndings (Buriel et al, 2004;Hughes & Bryan, 2002;Machado et al, 2009;Steiner, Mansur, Brucki, & Nitrini, 2008;Tallberg, Ivachova, Tingha, & Östberg, 2008;Tombaugh, Kozak, & Rees, 1999;Villodre et al, 2006), most likely due to population sampling and data analysis heterogeneous methods, such as reduced time for word searching. Ardila, Ostrosky-Solis, Rosselli, and Gomez (2000) proposed that education plays a complex role in cognition through the lifespan, in a way a single relationship between age and education cannot be established.…”
mentioning
confidence: 99%
“…Five seconds is also the given time for word generation during fMRI. As a comparison, the normative value for Swedish people at ages from 30 to 64 with ≤12 years of education is 42 words/minute (20). In addition, the test with sentence reading and completion outside the scanner showed that most patients probably did not have enough time to complete the sentences during the given time for fMRI scanning, which was 3 s. However, in most cases they were able to find a suitable word.…”
Section: Discussionmentioning
confidence: 99%